Switch-maintenance avelumab immunotherapy following first-line chemotherapy for patients with advanced, unresectable or metastatic urothelial carcinoma: the first Japanese real-world evidence from a multicenter study. (8th December 2022) - Miyake, Makito; Shimizu, Takuto; Oda, Yuki; Tachibana, Akira; Ohmori, Chihiro; Itami, Yoshitaka; Kiba, Keisuke; Tomioka, Atsushi; Yamamoto, Hiroaki; Ohnishi, Kenta; Nishimura, Nobutaka; Hori, Shunta; et al.
Abstract: Objective: To develop the first Japanese real-world evidence of switch-maintenance avelumab in advanced, unresectable or metastatic urothelial carcinoma (aUC). Methods: A multicenter-derived database registered 505 patients diagnosed with aUC between 2008 and 2021. Of these, 204 patients (40%) were selected and stratified according to the type of therapy used: maintenance avelumab group (27 [5.3%]), second-line (2 L) pembrolizumab group (103 [20%]) and 2 L cytotoxic chemotherapy group (74 [15%]). The progression-free survival and overall survival from the initiation of following therapy were compared. Tumor response was evaluated based on the Response Evaluation Criteria in Solid Tumors guideline v1.1 during the treatment period. A detailed analysis was performed in the maintenance avelumab group to investigate possible factors associated with response to avelumab therapy. Results: The maintenance avelumab group had a longer overall survival, not progression-free survival, compared with the other two treatment groups. The median treatment-free interval between the last dose of first-line (1 L) chemotherapy and the initiation of avelumab therapy was 6 weeks (range, 3–22). Disease control rate of maintenance avelumab therapy in patients with a treatment-free interval of ≤6 weeks was higher than that in patients with a treatment-free interval of >6 weeks (77 vs 40%, P  = 0.029). The patients showing objective response to 1 L chemotherapy were less likely to experience tumor relapse (4 of 19) after the initiation of avelumab therapy compared with those showing stable disease (7 of 8). Conclusions: Objective response to 1 L chemotherapy and early induction of maintenance avelumab therapy may be associated with increased benefit from maintenance avelumab therapy. Abstract : This study was the first to report the Japanese real-world evidence regarding the efficacy of maintenance avelumab in advanced urothelial carcinoma, serving as a benchmark for future researches.